PERENCANAAN STRUKTUR SEMARANG MEDICAL CENTER HOSPITAL JALAN KH. AHMAD DAHLAN SEMARANG - Khanif Setioadi; Dian Adi Prawoto; Windu Partono; Hardi Wibowo (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Semarang Medical Centre Hospital is a private hospital that contiuesly growing until today. SMC Hospital was built to fulfill the needs of society about the importance of health. In addition, SMC hospital was built to improve health service as the standard of international hospitals.The planning of structure of SMC Hospital based on SNI 1726 2012 concerning about the planning procedures of earthquake resistance. Structural system used is Special Moment Resisting Frames (SMRF). SAP2000 version 15 is used for modelling and building structure analysis. Stair structure was modelled separately and the result of reaction force was entried into the portal as load. Column, beam, and plate are modelled as one unity in the portal with significant specification.The analysis result from the structure are fundamental period and deflection, that will be compared with the limit-value in accordance with the rules. Meanwhile the analysis result in element such as moment, axial force, shear force and torsion are used to count section capacity based on SNI 2847:2013 about the requirement of structural concrete.